Did antepartum hypoxic insult caused by fetal vessel thrombosis influence the procalcitonin level in umbilical blood? A case report. Issue 11 (30th September 2015) - Kaneko, Masatoki; Yamauchi, Aya; Yamashita, Rie; Sato, Yuichiro; Kodama, Yuki; Sameshima, Hiroshi
Abstract: We report a case of marked elevation of the procalcitonin level in umbilical blood and neonatal blood at birth. The mother did not perceive fetal motion. Antepartum fetal heart rate monitoring showed a loss of variability and absence of acceleration. No fetal breathing movement, fetal movement, or fetal tone were observed by ultrasonography. The female neonate was delivered by cesarean section at 25 weeks of gestation, with birthweight 774 g. The umbilical arterial pH value at birth was 7.29. Mild elevation in interleukin‐6 and tumor necrosis factor‐α in umbilical blood were observed. Cytochrome c showed a high level in umbilical and neonatal blood at birth. Placental histopathology revealed multiple fetal vessel thrombosis in the large stem villi and chorionic vessels. The neonate showed no infectious signs throughout the neonatal period. Computed tomography at 3 months of age revealed atrophy in the cerebrum and cerebellum. At 1 year after birth, the infant showed spastic quadriplegia. In this case, antepartum asphyxia due to fetal vessel thrombosis may have influenced the elevation of procalcitonin level in umbilical blood and neonatal blood at birth.